1980
DOI: 10.1097/00000658-198007000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Muscle and Plasma Amino Acids Following Injury Influence of Intercurrent Infection

Abstract: The present study was undertaken to determine intracellular amino acid patterns in patients with multiple trauma, whether or not complicated by sepsis and during convalescence. A percutaneous muscle biopsy was performed three to four days following major accidental injury in ten patients and analyzed for muscle free amino acids. Venous blood was drawn at the time of the biopsy and analyzed for plasma free amino acids. Five patients developed sepsis and a repeat biopsy was performed on days 8 to 11. In five of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
0
5

Year Published

1982
1982
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 378 publications
(103 citation statements)
references
References 34 publications
8
90
0
5
Order By: Relevance
“…The marked depletion of the nonessential amino acids glutamate, serine, glutamine, glycine, arginine, and ornithine as well as the reduction in total plasma amino acids are similar to previous reports in patients with sepsis or severe trauma (12,13). In addition to the nonessential amino acids, the concentrations of isoleucine and lysine were also reduced in the septic patients.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The marked depletion of the nonessential amino acids glutamate, serine, glutamine, glycine, arginine, and ornithine as well as the reduction in total plasma amino acids are similar to previous reports in patients with sepsis or severe trauma (12,13). In addition to the nonessential amino acids, the concentrations of isoleucine and lysine were also reduced in the septic patients.…”
Section: Resultssupporting
confidence: 89%
“…Plasma amino acids were measured to assess the overall metabolic response in the septic patients and to get an indirect measure of the catabolic state in muscle. Previous studies have shown that typical changes in plasma amino acids occur in septic patients and that some of these changes may reflect muscle catabolism (10)(11)(12)(13).…”
Section: Methodsmentioning
confidence: 99%
“…20 -22 During periods of critical illness, glutamine is freely released from skeletal muscle and intracellular glutamine concentrations fall by more than 50%. 23,24 Individuals deficient in glutamine exhibit changes in gut morphology, including increased membrane permeability resulting in bacterial translocation, malabsorption and diarrhoea. Although the body can synthesize glutamine, it is currently considered to be a conditionally essential amino acid during periods of catabolism.…”
Section: Discussionmentioning
confidence: 99%
“…The amount of protein synthesis becomes limited with the use of decreased amino acids. Amino acid concentration, particularly glutamine, decreases in the skeletal muscles and plasma (26). The amount of intracellular amino acyl-tRNA transferase enzyme, which is responsible for protein synthesis of amino acids in ribosomes, is decreased in sepsis (25).…”
Section: Discussionmentioning
confidence: 99%